Domestication, Conservation, and Livelihoods: A Case Study of Piper peepuloides Roxb.—An Important Nontimber Forest Product in South Meghalaya, Northeast India. (27th March 2013) - Tynsong, H.; Dkhar, M.; Tiwari, B. K.
Abstract : Wild pepper ( Piper peepuloides Roxb., family: Piperaceae) is an evergreen climber which grows wild in tropical evergreen forests and subtropical evergreen forests of northeast India. This plant grows luxuriantly in the areas with high rainfall at lower elevations ranging from 100 to 800 m above mean sea level. In Meghalaya, to meet the market demand, farmers have domesticated it in arecanut agroforests and betel leaf agroforests. We found that the mean density of wild pepper in arecanut agroforest is 585 stem/ha and only 85 stem/ha in natural forest. In India, wild pepper is used in a variety of Ayurvedic medicines. Local people of Meghalaya uses powdered dry seeds mixed with honey and egg yolk for the treatment of severe cough. The study reveals that the average gross annual production of wild pepper is 7 quintals/ha, and final market price fetches Rs. 336, 000/ha, out of which 42% of the money goes to the grower, 16% to local trader, 23% to dealer, 17% to retailer, 1.2% to wages of labourers, and 0.6% to transport.